2018
DOI: 10.1111/bju.14455
|View full text |Cite
|
Sign up to set email alerts
|

Fertility managment in testicular cancer: the need to establish a standardized and evidence‐based patient‐centric pathway

Abstract: The underutilisation of semen analysis and sperm cryopreservation results in the failure to identify the azoospermic or severely oligozoospermic patient at diagnosis who may benefit from fertility-preserving procedures, for example, onco-microTESE at the time of orchidectomy. Fertility preservation and counselling needs to be broached earlier in the TC treatment pathway and made a greater priority. Given the advances in treatment, more patients with TC are surviving and looking to return to a normal life. Pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 90 publications
(172 reference statements)
0
52
1
1
Order By: Relevance
“…In this study, 46.2 % patients with leukaemia and lymphoma had no spermatozoa to freeze. Some reports have shown that leukaemia patients have an innate suppression of spermatogenesis through an unknown mechanism [ 19 – 21 ]. In practice, a few cancer patients visiting our unit give up sperm preservation owing to the cost.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 46.2 % patients with leukaemia and lymphoma had no spermatozoa to freeze. Some reports have shown that leukaemia patients have an innate suppression of spermatogenesis through an unknown mechanism [ 19 – 21 ]. In practice, a few cancer patients visiting our unit give up sperm preservation owing to the cost.…”
Section: Discussionmentioning
confidence: 99%
“…There are several causes of semen quality decline before cancer treatment, such as disruption of the blood-testis barrier and endocrine derangements [18,19]. Some studies show that cancer patients especially leukemia patients have an innate suppression of spermatogenesis, but the mechanism for suppression is under studied [15,20,21]. So, not so paradoxically, testicular tumors needing removing one testicle and blood tumor (including Hodgkin's lymphoma, non-Hodgkin's lymphoma and leukemia) causing fever both resulted in lower sperm concentrations than other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…79,[82][83][84] Approximately half of the patients with newly diagnosed TC have low sperm counts (,20 million/mL), decreased motility indices (,40%), and large percentages of abnormal sperm cells before receipt of any RT or chemotherapy. 85 A systematic review 86 reported that 6% to 24% of TCS are azoospermic and 50% oligozoospermic at TC diagnosis. Because spermatogonia are highly sensitive to RT, 87 scattered irradiation of the remaining testicle during abdominal RT can adversely affect short-term reproductive function of TCS.…”
Section: Hypogonadismmentioning
confidence: 99%